A Randomized Controlled Trial to Examine the Relationship Between Peer Mentoring for Physical Activity and Cardiometabolic Health - Moradeke Bamgboye; David Adeyemi; Emmanuel Agaba; Susan Yilme; Clement A. Adebamowo; Sally N. Adebamowo (Ubiquity Press, 2023)
Background: Studies examining the effect of peer mentoring on physical activity levels have been conducted in mostly elderly and young populations, and the results have been inconsistent. This study examined the impact of one-on-one peer mentoring on physical activity and cardiometabolic parameters in urban adults. Methods: The study participants were 353 overweight or obese adults residing in Abuja, Nigeria. They were randomized into two groups, peer-mentored (n = 128) and a control (n = 225) group. All the participants received nutritional counseling and were invited to attend instructor-led physical activity sessions each week for six months. Differences in the frequency, duration, and intensity of physical activity and cardiometabolic parameters, including body fat, muscle mass and lipids, were evaluated within and between the groups with t and rank sum tests. Results: At the end of the study period, the average time spent on physical activity increased significantly by 14% (p = 0.006), and the average time spent on vigorous physical activity increased by 99% (p = 0.003) compared to baseline for participants in the peer-mentored group. For those in the control group, the average time spent on physical activity decreased significantly by 7% (p = 0.03), while the average time spent on vigorous physical activity increased by 30%, but this was not statistically significant (p = 0.34). In both groups, there were significant improvements in the total cholesterol, low- and high-density lipoproteins and triglycerides levels, at the end of the study period, compared to baseline. Conclusions: In these overweight or obese adults, we observed that peer mentoring was positively associated with increased physical activity. Peer mentoring also holds great promise for improving cardiometabolic health and promoting a healthy lifestyle in adults.